Concept Mapping in Social Research - Pokharel, Bharat (Tribhuvan University Journal, 2010)
Social scientists conduct research on two distinct but interrelated levels:conceptual-theoretical and observational-empirical. More precisely, social researches involve a constant interplay of two process: theory construction and theory testing. For example, it is a fact that in the last 100 years social mobility has increased. This fact in not merely based on random observation, but is an empirically verified statement about phenomena. This involves both a scientific observation and a predetermined conceptual-theoretical framework by which the observation is guided. In this article, the conceptual theoretical level of social research has been explained with the help of the basic elements such as concept and concept mapping. Key Words: Mapping; Social; Research Tribhuvan University Journal Vol. XXVI, No. 1, 2009 Page: 1-6